The Accuracy of the Clinical Carpal Tunnel Syndrome Diagnosis before the Nerve Conduction Studies - Atkočiūnas, A.; Šimkutė, A.; Mameniškienė, Rasa (Neurologijos seminarai, 2024)
Background and aim: Carpal tunnel syndrome (CTS) is a compressive neuropathy caused by compression of the median nerve in the carpal tunnel. It is the most common entrapment neuropathy. According to different studies, the prevalence of CTS among adults (15–65 years old) in Western Europe ranged from 0.29% to 43%. CTS affects middle-aged active workers and is associated with high healthcare costs and a hefty economic burden. It is thus essential to diagnose CTS early and refer the patient to further investigation and treatment. In this study, we aimed to evaluate the accuracy of the clinical CTS diagnosis before the nerve conduction studies were performed on the referred patients.Methods: The concordance of clinical diagnoses was assessed by comparing referral diagnoses with diagnoses confirmed by electroneuromyography. All the patients referred for electroneuromyography to Mykolas Marcinkevičius Hospital between August 2023 and February 2024 were included in this research. The age, sex, referral and final diagnoses of the enrolled patients were taken from their outpatient charts. The obtained data were summarized and processed with Microsoft Office Excel 365, and the data analysis was performed with IBM SPSS Statistics.Results: The most common reasons that patients were referred to perform NCS were suspected carpal tunnel syndrome (30.7%), cubital tunnel syndrome (13.5%), other upper extremity mononeuropathies (16.2%), and polyneuropathies (15.5%). The most common diagnosis after consultation was carpal tunnel syndrome (42.6%), followed by pathologies of nerve roots or plexuses (14.5%). Out of 91 patients referred to electroneurography due to suspicion of CTS, 67 (73.6%) were confirmed cases, whereas, for 12 (13.2%) patients, no abnormalities were detected during NCS.Conclusion: Our analysis supports the theory that the electrodiagnostic examination is essential to specify and confirm the diagnosis of CTS, thus avoiding hyperdiagnosis and preventing patients from excessive surgical treatment.